The ratio of morning cortisol to CRP prospectively predicts first-onset depression in at-risk adolescents. (July 2021) - Landau, E.R.; Raniti, M.B.; Blake, M.; Waloszek, J.M.; Blake, L.; Simmons, J.G.; Schwartz, O.; Murray, G.; Trinder, J.; Allen, N.B.; Byrne, M.L.
Abstract: Rationale: Early-onset adolescent depression is related to poor prognosis and a range of psychiatric and medical comorbidities later in life, making the identification of a priori risk factors for depression highly important. Increasingly, dysregulated levels of immune and neuroendocrine markers, such as C-reactive protein (CRP) and cortisol, have been demonstrated as both precursors to and consequences of depression. However, longitudinal research with adolescent populations is limited and demonstrates mixed immuno-endocrine-depression links. Objective: This study explored the putative bidirectional relationship between salivary measures of cortisol (Cort) and CRP, including the novel Cort:CRP ratio and depression. Methods: Participants from the randomized control trial 'Sleep and Education: learning New Skills Early' (SENSE) Study were 122 adolescents at risk for depression (73 females) aged 12–16 years ( M = 12.71 years, SD = 1.01 years) assessed at baseline (T1), post-intervention (T2), and a two-year follow-up (T3). Results: Logistic regression results demonstrated that adolescents with higher T1 Cort:CRPmorn ratio levels were two-fold more likely to develop a first-onset depressive disorder from T2 to T3 as compared to adolescents with lower Cort:CRPmorn ratio levels, β = 0.73, t (36) = 2.15, p = .04, OR = 2.08. This effect was not moderated by treatment condition ( β = −1.38, t (13) = -1.33, p = .20) and did not change when controlling for known risk factors for depression, including sex, age, body-mass index, socio-economic status, T1 anxiety disorder, nor T1 sleep disturbance, anxiety, or depressive symptoms ( β = 0.91, t (31) = 2.14, p = .04). Conclusion: Results highlight potential immuno-endocrine dysregulation as an underlying risk factor for adolescent first-onset depression, and may inform the development of targeted, preventative biobehavioral treatment strategies for youth depression. Highlights: Adolescent depression is related to risk for medical comorbidities later in life. We studied longitudinal links between depression and immuno-endocrine markers. Markers included the ratio of morning cortisol to C-reactive protein levels. The ratio predicted first-onset adolescent depression in a longitudinal design. Immuno-endocrine dysregulation may be a risk factor for adolescent depression.